Wearing Virtue: Plato’s Republic V, 449a-457b and the Socratic Debate on Women’s Nature - Arruzza, Cinzia (Revista Archai, 2023)
In Plato’s Republic V, 449a-457b, Socrates argues that the guardian class of Kallipolis will comprise both men and women and that women with the appropriate nature ought to receive the same education and fulfill the same tasks as their male counterparts. In this article I argue, against competing interpretations of this claim as dependent either on the necessity of abolishing the oikos or on eugenic principles, that Socrates’ argument ought to be understood as a genuine argument about women’s natural capabilities and ought to be interpreted in light of the Socratic debate about women’s virtues. Moreover, I show that the legal language mobilized, combined with polemical references to Aristophanes, serves the purpose of evoking Socrates’ trial, thus alerting the reader to the seriousness of the proposal in question.